2017
DOI: 10.1016/j.bbadis.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ataxia telangiectasia porcine model phenocopies the multisystemic features of the human disease

Abstract: Ataxia telangiectasia (AT) is a progressive multisystem autosomal recessive disorder caused by mutations in the AT-mutated (ATM) gene. Early onset AT in children is characterized by cerebellar degeneration, leading to motor impairment. Lung disease and cancer are the two most common causes of death in AT patients. Accelerated thymic involution may contribute to the cancer, and recurrent and/or chronic respiratory infections may be a contributing factor to lung disease in AT. AT patients have fertility issues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A major factor limiting our ability to define why loss of DDR proteins, like ATM, selectively impacts the cerebellum and causes progressive ataxia is the lack of an animal model that recapitulates these neurological symptoms (Lavin 2013). Several A-T rodent models have been created over the past several years by inserting gene mutations that cause protein dysfunction (lack kinase activity) or complete deficiency (Herzog et al 1998;Xu and Baltimore 1996;Elson et al 1996;Spring et al 2001;Campbell et al 2015;Quek et al 2016;Tal et al 2018;Lavin 2013); a minipig was also recently reported (Beraldi et al 2017). However, none develop an overt, progressive ataxia with cerebellar dysfunction and atrophy that recapitulates the human disease, even though other aspects of the disorder like thyroid cancers, infertility, and immune abnormalities do develop.…”
Section: Introductionmentioning
confidence: 99%
“…A major factor limiting our ability to define why loss of DDR proteins, like ATM, selectively impacts the cerebellum and causes progressive ataxia is the lack of an animal model that recapitulates these neurological symptoms (Lavin 2013). Several A-T rodent models have been created over the past several years by inserting gene mutations that cause protein dysfunction (lack kinase activity) or complete deficiency (Herzog et al 1998;Xu and Baltimore 1996;Elson et al 1996;Spring et al 2001;Campbell et al 2015;Quek et al 2016;Tal et al 2018;Lavin 2013); a minipig was also recently reported (Beraldi et al 2017). However, none develop an overt, progressive ataxia with cerebellar dysfunction and atrophy that recapitulates the human disease, even though other aspects of the disorder like thyroid cancers, infertility, and immune abnormalities do develop.…”
Section: Introductionmentioning
confidence: 99%
“…Porcinecentered online tools and databases are now available 61 . Genetic manipulation of pigs (including knockouts, tissue-specific transgenics, inducible expression 30,[62][63][64][65][66][67][68][69] ) with similar tools as used in the mouse is becoming more routine, with new gene-edited porcine models emerging for diseases such as atherosclerosis, cystic fibrosis, Duchenne muscular dystrophy, and ataxia telangiectasia 70,71 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in genome editing have given us the ability to generate bespoke mutations in almost any species required in order to fill translational gaps with physiologically relevant models [ 15 ]. The most ethically viable and physiologically appropriate systems for neurological modelling are of livestock origin (sheep and pig) [ 16 , 17 , 18 , 19 ]. Yet, there are a limited number of publications that cover neurological assessment specifically in livestock [ 13 , 14 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%